2022
DOI: 10.5194/isprs-archives-xlvi-3-w1-2022-155-2022
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Ble 5.1 New Feature Angle of Arrival for Relative Positioning

Abstract: Abstract. The official release of Bluetooth Core Specification, version 5.1 in 2019, provides a new feature for direction determination. It introduces a fine-grained angle measurement capability including Angle of Arriva (AoA) and Angle of Departure, which is deemed essential to the development of Internet of Things applications for localization or relative positioning within the area where Global Navigation Satellite System signals cannot be received. In this paper, we set up a series of experiments to empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…To improve accuracy, direction-finding enhancements were introduced in the BLE 5.1 specifications, namely support for Angle of Arrival (AoA) and Angle of Departure (AoD). Several researchers have conducted empirical studies to evaluate the accuracy of BLE's AoA technique [24], [25], but mainly for static targets and using only a limited number of tested locations. Recently, Pau et al [26] have used a hybrid solution based on both RSSI and AoA information that results in an average distance error of 0.7 m. However, the authors tested only a few locations and did not describe in detail how these were chosen nor the impact of dense multipath on RSSI-based measurements.…”
Section: A Bluetooth Low Energymentioning
confidence: 99%
See 1 more Smart Citation
“…To improve accuracy, direction-finding enhancements were introduced in the BLE 5.1 specifications, namely support for Angle of Arrival (AoA) and Angle of Departure (AoD). Several researchers have conducted empirical studies to evaluate the accuracy of BLE's AoA technique [24], [25], but mainly for static targets and using only a limited number of tested locations. Recently, Pau et al [26] have used a hybrid solution based on both RSSI and AoA information that results in an average distance error of 0.7 m. However, the authors tested only a few locations and did not describe in detail how these were chosen nor the impact of dense multipath on RSSI-based measurements.…”
Section: A Bluetooth Low Energymentioning
confidence: 99%
“…To improve the accuracy of the AoA technique, researchers have proposed algorithms based on non-linear recursive least square and unscented Kalman filters to reduce multipath and antenna switching errors [27]. Unfortunately, the choice of channel greatly impacts the direction-finding techniques [24], [25], and the angular error spreads more at lower frequencies [5]. An empirical study using softwaredefined radios demonstrated the effectiveness of the AoA technique in achieving sub-metre accuracy when tracking moving targets [5]; however, measurements were carried out in an outdoor environment with few multipath reflections, and information from several packets was averaged to obtain the reported accuracy.…”
Section: A Bluetooth Low Energymentioning
confidence: 99%
“…The location accuracy that can be expected from BLE 5.0 is about 2-5m [1,2]. In 2019, BLE 5.1 was released which included new metrics for positioning, Angle of Arrival (AoA) and Angle of Departure (AoD), that enables Direction Finding feature 2 within BLE devices [3]. With this new addition to the newer BLE 5.1 version, location accuracy down to below 1.0m, known as sub-meter level accuracy can be expected [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…DT and GBA are tested against online training dataset.2. TDT and ODT machine learning models are trained 3…”
mentioning
confidence: 99%